A redox-active [3]rotaxane capable of binding and electrochemically sensing chloride and sulfate anions. - Evans, N; Serpell, C; Beer, P (2011)
A ferrocene functionalised redox-active [3]rotaxane which contains two interlocked anion recognition sites has been prepared by chloride anion templation. With chloride two equivalents of anion are bound, one in each of the interlocked cavities, while sulfate forms a 1:1 stoichimetric sandwich type complex; the rotaxane can also electrochemically sense the two anions in acetonitrile.